2015
DOI: 10.3748/wjg.v21.i17.5311
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and costs of laparoscopic pancreaticoduodenectomy during the initial learning curvevslaparotomy

Abstract: TLPD is safe when performed by experienced pancreatobiliary surgeons during the initial learning curve, but has a higher cost than open pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 28 publications
3
53
0
1
Order By: Relevance
“…Since the beginning of this decade, several reports from other centres have documented comparative data for these two procedures. However, until now, no randomized trial existed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of this decade, several reports from other centres have documented comparative data for these two procedures. However, until now, no randomized trial existed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies aimed at assessing the potential value of LPD with respect to obtaining negative retroperitoneal margin may be warranted. Further, this study does not account for the impact of a learning curve when implementing LPD that associates with increased OR time, but not necessarily increased complications [6, 13, 19, 22]. Specific to increased OR time that would impact cost, this learning curve is realized somewhere between ten and fifty cases [6].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies have identified potential benefits to LPD including decreased blood loss, delayed gastric emptying rates, hospital length of stay, wound infection rates, and utilization of intensive care services, while facilitating larger percentages of patients proceeding on to adjuvant therapy [611]. These benefits even appear to be realized during the institutions early experience with LPD [6, 13, 14]. Further, there does not appear to be a clinically meaningful difference between the approaches with respect to surrogate markers of oncologic adequacy including positive margin rates [6, 810] and number of resected lymph nodes [6, 810, 13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations